Tingkat Pengetahuan Kader Posyandu tentang Pentingnya Pemeriksaan Denver Development Screening Test (DDST) di Posyandu Wilayah Kerja Puskesmas Karya Wanita Rumbai Pekanbaru - Norlita, Wiwik; isnaniar, Isnaniar; Wulandari, Nurfitri (As-Shiha: Jurnal Kesehatan, 2021)
In the development of toddlers, cadres have a role in counseling parents (Mothers) regarding child health, monitoring and stimulation/stimulation/early developmental stimuli as well as reporting to health facilities when finding a child who is late in development.. Judging by child health problemsthere is a rate of developmental deviation in children about 10-17 percent. In order to overcome this, early detection is necessary as an effort to plan the implementation program, and determine the prognosis. The purpose of the study was to find out "an overview of the posyandu cadre's knowledge of the importance of the denver development screening test". This research was conducted on August 6-8, 2020, using qualitative descriptive methods by sampling using Purposive sampling from one cadre in each posyandu of puskesmas working area by tassel women, with a total of 36 cadres. Data retrieval or instrument in the form of questionnaires, then analyzed using percentages. With the results of the respondent's knowledge well categorized as 2 respondents (5.6%), enough as many as 21 respondents (58.3%), and less as many as 13 respondents (36.1%). Cadre knowledge of the importance of DDST inspection in general is sufficient. Therefore, it is expected that there is an effort from puskesmas to further improve the knowledge of cadres through counseling about DDST examination.